2020
DOI: 10.21037/qims.2019.10.07
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of common extensor tendon elasticity in patients with lateral epicondylitis using shear wave elastography

Abstract: Background: To investigate the role of shear wave elastography (SWE) in patients with lateral epicondylitis (LE) by assessing the common extensor tendon (CET) elasticity.Methods: A total of 62 unilateral LE patients were enrolled. Shear wave speed (SWS) and the thickness of CET in both elbows, along with the involved elbows with pre-and post-treatment, were obtained by SWE. The differences between groups, inter-and intra-observer agreements, and diagnostic accuracy were analyzed with a paired t-test, intraclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 31 publications
6
33
1
Order By: Relevance
“…Conversely, stiffness of abnormal tendons is decreased 22 . The CET stiffness values obtained in our study are consistent with those of a previous study of lateral epicondylitis using the same ultrasound apparatus and methodology 23 . Tendon overuse is the main pathogenic mechanism in the onset of common extensor tendinopathy.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Conversely, stiffness of abnormal tendons is decreased 22 . The CET stiffness values obtained in our study are consistent with those of a previous study of lateral epicondylitis using the same ultrasound apparatus and methodology 23 . Tendon overuse is the main pathogenic mechanism in the onset of common extensor tendinopathy.…”
Section: Discussionsupporting
confidence: 91%
“…27 Accordingly, elastography has been suggested as a diagnostic tool for the evaluation of lateral epicondylitis. 23 However, our findings suggest that CET stiffness decreases in patients with CTS, even without symptomatic lateral epicondylitis, and thus should not be relied upon in isolation. Our study has several limitations.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The ultrasound system propagates shear waves into tissues and assesses their elastic modulus. This has been used in a variety of musculoskeletal conditions including the rotator cuff tendons ( 16 , 17 ) , epicondylitis ( 18 ) , and Achilles ( 19 ) . Wu et al reported that in patients with clinical findings consistent with adhesive capsulitis shear wave elastography demonstrated that the CHL was significantly stiffer in the symptomatic shoulder compared with the asymptomatic shoulder ( 13 ) .…”
Section: Introductionmentioning
confidence: 99%